PENERAPAN PENALARAN EMPATI DALAM PSIKOLOGI SOSIAL SEBAGAI UPAYA MENINGKATKAN NALAR SOSIAL DALAM MASYARAKAT - Misbahudin, Misbahudin; Setiyawan, Rendi; Faris, Ahmad Zidan; Shafira, Rina; Sari, Ika Tri Rachma; Novalia, Afifah Affni; Munawaoh, Hidayatu (Jendela PLS, 2025)
The method used is a qualitative method with the Library Research model, which means that the researcher will collect various information that is relevant to the problem topic being researched, obtained from scientific books, research reports, scientific essays, appropriate theses and encyclopedias. and other sources that support the articles presented. Psychology and empathy are two key factors that play an important role in social relationships and a person's quality of life. This article discusses strategies for developing emotional intelligence in terms of empathy in everyday life. Through a deeper understanding of oneself and others, as well as the application of practices such as active listening, managing emotions, and strengthening communication, individuals can increase their ability to interact with their environment more effectively. Thus, the goal of developing psychological understanding and empathy will not only have a positive impact on interpersonal relationships but also the mental health and general well-being, especially of those around them.